Arousal/Stress Effects of "Overwatch" eSports Game Competition in Collegiate Gamers. Issue 10 (21st October 2022) - Kraemer, William J.; Caldwell, Lydia K.; Post, Emily M.; Beeler, Matthew K.; Emerson, Angela; Volek, Jeff S.; Maresh, Carl M.; Fogt, Jennifer S.; Fogt, Nick; Häkkinen, Keijo; Newton, Robert U.; Lopez, Pedro; et al.
Abstract: Kraemer, WJ, Caldwell, LK, Post, EM, Beeler, MK, Emerson, A, Volek, JS, Maresh, CM, Fogt, JS, Fogt, N, Häkkinen, K, Newton, RU, Lopez, P, Sanchez, BN, and Onate, JA. Arousal/stress effects of "Overwatch" eSports game competition in collegiate gamers. J Strength Cond Res 36(10): 2671–2675, 2022—To date, no physical response data are available for one of the most popular eSport games, Overwatch . The purpose of this investigation was to describe the stress signaling associated with competitive Overwatch play and to understand how acute hormonal responses may affect performance. Thirty-two male college-aged gamers (age: 21.3 ± 2.7 years; estimated time played per week: 18 ± 15 hours) completed the study. Subjects were randomly assigned to a 6-player team to compete in a tournament-style match. Salivary measures of cortisol and testosterone were collected immediately before (PRE) and after (POST) the first-round game, with the heart rate recorded continuously during the match. The mean characteristics were calculated for each variable and comparisons made by the skill level. Significance was defined as p ≤ 0.05. There were no differences in measures of salivary cortisol. A differential response pattern was observed by the skill level for testosterone. The low skill group displayed a significant increase in testosterone with game play (mean ± SD, testosterone PRE: 418.3 ± 89.5 pmol·L −1, POST: 527.6 ± 132.4 pmol·L −1, p < 0.001), whereas no change was observed in the high skill group. There were no differences in heart rate characteristics between skill groups. Overall, the average heart rate was 107.2 ± 17.8 bpm with an average max heart rate of 133.3 ± 19.1 bpm. This study provides unique physiological evidence that a sedentary Overwatch match modulates endocrine and cardiovascular responses, with the skill level emerging as a potential modulator.